Do charter schools receive their fair share of funding? School finance equity for charter and traditional public schools - Knight, David S.; Toenjes, Laurence A. (Education Policy Analysis Archives, 2020)
U.S. charter schools are publicly funded through state school finance formulas that often mirror the traditional public school finance systems. While charter school advocates and critics disagree over whether charters receive an equitable share of funding, few discussions are based on rigorous analyses of funding and expenditures. Most prior analyses, especially those presented in policy briefs or white papers, examine average funding differences without exploring underlying cost factors between the two sectors. Our purpose is to demonstrate how careful analysis of charter school funding with appropriate methodological approaches can shed light on disagreements about charter school finance policy. Using detailed school finance data from Texas as a case study, we find that after accounting for differences in accounting structures and cost factors, charter schools receive significantly more state and local funding compared to traditional public schools with similar structural characteristics and student demographics. However, many small charter schools are actually underfunded relative to their traditional public school counterparts. Policy simulations demonstrate that on average, each student who transfers to a charter school increases the cost to the state by 1,500. We discuss the implications of these findings for both school finance policy in Texas and nationally.